Adsorption Equilibrium for Heavy Metal Divalent Ions (Cu2+, Zn2+, and Cd2+) into Zirconium-Based Ferromagnetic Sorbent - Yung, Agnes Weng Lee; Soh, Fong Lim; Chua, David Sing Ngie; Khairuddin, Sanaullah; Rubiyah, Baini; Mohammad Omar, Abdullah (Hindawi Publishing Corporation, 2017)
Zirconium-based ferromagnetic sorbent was fabricated by coprecipitation of Fe2+/Fe3+ salts in a zirconium solution and explored as a potential sorbent for removing the Cu2+, Zn2+, and Cd2+ from aqueous solution. The sorbent could easily be separated from aqueous solution under the influence of external magnetic field due to the ferromagnetism property. A trimodal distribution was obtained for the sorbent with average particle size of 22.74